Pengaruh Mutu Produk, Desain Dan Nilai Pelanggan Terhadap Loyalitas Konsumen Pada Batik Gabovira - Evi Meidasari; Meliana Meliana; Niken Kusumawardani (Inovatif: Jurnal Ekonomi, Manajemen, Akuntansi, Bisnis Digital dan Kewirausahaan, 2022)
This research was carried out todetermine whether factors-factors of product quality, design and customer value affects consumer loyalty. The object in this research is Gabovira batik.  The sample numbered 92 respondents taken using purposive sampling technique. The independent variables consisted of product quality (X1), design (X2) and the value of customer (X3). The dependent variable is the loyalty of consumers (Y). Data analysis using SPSS 21 include: reliability test, test the validity of the assumptions of multiple regression analysis, classical and hypothesis testing through the F-test and T-test, as well as the analysis of the coefficient of determination (R2). From the results of this research note that product quality and designs have significantly to influence the loyalty of consumers, while the value of the customers do not have influence significantlyto consumer loyalty.F test results show that the product quality, design and value customers significant effect simultaneously againts the loyalty of consumers. Where as the results of the determinations (R2) show the influence of the quality of the products (X1), design (X2) and value of customers (X3) againts the loyalty of consumers (Y) of 16.5%. And the remainst affected by promotion, people and unvariable factors of 83.5%.